HUBUNGAN SIKAP, PELATIHAN K3, KETERSEDIAAN APD DENGAN KEJADIAN KECELAKAAN KERJA DI PROYEK SEKOLAH KRISTEN CALVIN PT. TOTAL BANGUN PERSADA TBK TAHUN 2022 - Ervina Dyah Azrinindita; Affan Ahmad; Astrid Novita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The construction sector is a dynamic field that contains the risk of accident hazards. In 2022, at the Calvin Christian School Project there was a work accident caused by human and machine factors. The purpose of this study was to determine the factors related to work accidents among workers at PT. Total Bangun Persada, Tbk Calvin Christian School Project in 2022. This type of research is quantitative with a cross-sectional research design, namely research that observes subjects with a single approach and is carried out only once. The sample is construction workers as many as 83 construction workers. The instruments in this study used measurements and questionnaires regarding attitudes, OSH training and the availability of PPE. Data analysis was performed univariately and bivariately using the chi-square test. Based on the results of the study it was found that there was a significant relationship between attitude and the incidence of work accidents using the chi-square test (p=0.004 <0.05) with an OR of 3.911. There is a significant relationship between OSH training and the incidence of work accidents from the chi-square test result (p=0.034 <0.05), there is a significant relationship between the availability of personal protective equipment and the incidence of work accidents from the chi-square test result (p=0.001 <0.05 ). It is hoped that the project management will be able to improve the attitude of workers who do not comply with using personal protective equipment, as well as hold regular OSH training and monitor PPE supplies so that PPE is available.